2015
DOI: 10.1002/acr.22581
|View full text |Cite
|
Sign up to set email alerts
|

Knee Extensor Muscle Strength in Middle‐Aged and Older Individuals Undergoing Arthroscopic Partial Meniscectomy: A Systematic Review and Meta‐Analysis

Abstract: Objective. People with meniscal tears are at high risk to develop or progress to knee osteoarthritis. Knee extensor weakness is considered a risk factor for osteoarthritis and is often reported in these individuals. The purpose of this systematic review and meta-analysis was to investigate knee extensor strength in people undergoing an arthroscopic partial meniscectomy (APM). Methods. Six databases (Medline, CINAHL, SPORTDiscus, Embase, PEDro, and AMED) were searched up to June 22, 2014. Studies that measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…Muscle strength at three months for the first 82 patients has been previously reported 15. A recent meta-analysis of surgically treated patients found that weakness of the extensor muscle already existed in legs before surgery, and this remained largely for at least four years after surgery 16. Considering these results, we did not think that obtaining muscle function at 24 months in addition to at 12 months would have changed the interpretation of our results.…”
Section: Methodssupporting
confidence: 53%
“…Muscle strength at three months for the first 82 patients has been previously reported 15. A recent meta-analysis of surgically treated patients found that weakness of the extensor muscle already existed in legs before surgery, and this remained largely for at least four years after surgery 16. Considering these results, we did not think that obtaining muscle function at 24 months in addition to at 12 months would have changed the interpretation of our results.…”
Section: Methodssupporting
confidence: 53%
“…We hypothesized that high knee extensor strength may be particularly important to delay or prevent knee OA development in participants already at higher risk of knee OA, such as those with medial meniscal pathology. Indeed, a recent systematic review and meta-analysis revealed that thighs of middle-aged and older individuals undergoing meniscal surgery show reduced knee extensor muscle strength both prior to surgery and up to 48 months after surgery (14). The results of the present study only partially confirm our hypothesis, as we observed a protective effect of high knee extensor muscle strength only for incident radiographic knee OA in women.…”
Section: Discussionmentioning
confidence: 99%
“…Knee pathology in general is known to be associated with impaired muscle function (14,15); thus individuals with a combination of knee injury or degenerative meniscal tears and low muscle strength may be at particularly high risk for knee OA. Indeed, a recent systematic review and meta-analysis reported middle-aged and older patients who had undergone meniscectomy to have impaired knee extensor strength up to 4 years post surgery (14). However, the importance of this impaired knee extensor strength in the risk for later knee OA has not been investigated in individuals with meniscal pathology.…”
Section: Introductionmentioning
confidence: 99%
“…; Hall et al. ; Jones and Wortmann ), as well as by training/fitness level (Fiatarone et al. ; Bousquet‐Santos et al.…”
Section: Introductionmentioning
confidence: 99%
“…Praagh and Dor e 2002; Kasper 2011;Costa et al 2012;Landi et al 2012Landi et al , 2015Garatachea and Lucia 2013;Giordani and Puri 2013), presence of musculoskeletal diseases (Felin et al 2007;Henriksen et al 2009;Winters and Rudolph 2014;Colombo et al 2015;Davis et al 2015;Hall et al 2015;Jones and Wortmann 2015), as well as by training/fitness level (Fiatarone et al 1990;Bousquet-Santos et al 2006;Arnold and Bautmans 2014;Chung…”
mentioning
confidence: 99%